If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + 4 = 2n + 33 Reorder the terms: 4 + 5n = 2n + 33 Reorder the terms: 4 + 5n = 33 + 2n Solving 4 + 5n = 33 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 4 + 5n + -2n = 33 + 2n + -2n Combine like terms: 5n + -2n = 3n 4 + 3n = 33 + 2n + -2n Combine like terms: 2n + -2n = 0 4 + 3n = 33 + 0 4 + 3n = 33 Add '-4' to each side of the equation. 4 + -4 + 3n = 33 + -4 Combine like terms: 4 + -4 = 0 0 + 3n = 33 + -4 3n = 33 + -4 Combine like terms: 33 + -4 = 29 3n = 29 Divide each side by '3'. n = 9.666666667 Simplifying n = 9.666666667
| 3(a+7)=36 | | a^5+4=15 | | C/3C | | 4x-11=46 | | 3x+5=-8x-4 | | 4t-9=0 | | 7m+5=55 | | 1.74x+x=.1 | | 6h-3=15 | | 3g+6=15 | | x/3+x/12=15/4 | | 4/x=5/-6 | | 3n^2+6n-13=0 | | R=ir | | (2x-3)*(2x-3)=25 | | 6+6x=4x-10 | | Y=(x-2)(x+3) | | 4sint+3cost=0 | | 3x+30=2x-10 | | Y=(x+4)(x+1) | | Y=(x+4)(c+1) | | 12w=14 | | w/4=7.2 | | -7x+5=1-3x | | 23x+14-14=7x-2-14 | | 2y(8-2y)= | | Sinx+x*cosx-sinx=0 | | F(x)=2x^3-5x^2+4-1 | | 7(w+10)+6=12w-12 | | 4x*x+29x-24=0 | | 7x-14=4x-23 | | xy+yf-dx=0 |